Methodology of technology mapping in Vietnam - Dung, Ta Viet; Dung, Nguyen Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This paper introduce methodology of technology mapping in Vietnam, in which includes technology map for industries, products and technology fields. Technology mapping will provide some specific information of technological status, gap among technologies in the world. Authors also analyses the status and trend of technology development, regional and world market. It provides the important information for management agencies, research institutes, training organizations, associations and other enterprises in industry. The technology maps primarily distinguished in structure of technology maps as defining the objectives, scope, technology tree, market analysis or technology application. Code: 16081802